(untitled) (Research, Society and Development, 2022)
Introduction: Bone Marrow Transplantation (BMT) is a treatment with important curative potential, which raises great hope in patients experiencing diseases that pose a serious threat to the continuity of life. However, such treatment is permeated by high risks, in addition to the possibility of relapse of the disease still existing after it, thus, it is important to consider care approaches that cover this unpredictability, such as Palliative Care. Objective: To describe the contributions of the palliative care approach in bone marrow transplantation, which is characterized as a treatment with a curative proposal for patients with diseases that pose a serious threat to the continuity of life. Method: Integrative Literature Review carried out in the Scopus, PubMed, PsychINFO and LILACS databases, covering studies from 2011 to 2021. The studies were categorized based on content analysis. Results: After applying the exclusion criteria, six studies remained that made up the corpus of this work. Results showed that the early integration of palliative care into standard BMT care significantly contributes to the management of physical and emotional symptoms, exploration of topics not addressed by other professionals, such as coping with the moment, as well as discussions about advance care planning. Conclusion: Palliative Care adds numerous gains in relation to the care of the patient undergoing BMT. However, there is a scarcity of studies involving both themes and the need to develop new studies that can promote this practice within BMT clinics.